Study of a High Temperature–Resistant Shielding Material for the Shielding Doors of Nuclear Power Plants - Xiao-ling, LI; Rong-jun, Wu; Xiao-hui, Xu; Duo-fei, Zhang; Ming, YU (Frontiers in Energy Research, 2021)
An optimization design and application of high temperature–resistant shielding material was carried out according to the nuclear power plant source characteristics and special protection requirements such as loss-of-coolant accident (LOCA). The composition of lead–boron polyethylene shielding composite was optimized based on the genetic algorithm and Monte Carlo methods and then realized by blending modification and graft copolymerization to improve its high temperature–resistant, shielding, and mechanical properties. Then comprehensive properties such as mechanical, neutron shielding, damp heat aging, irradiation resistance, and high temperature resistance were tested. These experiments proved that the high temperature–resistant lead–boron polyethylene shielding composite has excellent performance; especially, as it is able to keep a complete structure in a high-temperature environment of up to 190°C for 48 h. Finally, the shielding composite was applied to the shielding door design of a reactor pit chamber. When the shield thickness is 60 mm, the level of the neutron dose rate was reduced by 10 times, and that of the γ dose rate was reduced by 5 times, which meets all the requirements of radiation protection safety for nuclear power plants.